2011
DOI: 10.1177/0148607110387799
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Post–Ligament of Trietz Nasojejunal Feeding in Enteral Nutrition and the Need for Improved Feeding Tube Design and Placement Methods

Abstract: Nutrition support is an important link in the chain of therapy for intensive care unit patients. The early institution of nutrition support significantly reduces the incidence of septic complications, reduces mortality, and shortens hospital stay. Unfortunately, impaired gastrointestinal function, particularly gastric atony, restricts the use of nasogastric enteral tube feeding, and the use of this route of administration in these patients can lead to regurgitation, aspiration, and the development of pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…8514 July 14, 2014|Volume 20|Issue 26| WJG|www.wjgnet.com [212] . However, while feeding via PEG may reduce the risk of aspiration, it will not eliminate it altogether [164] , especially in patients in whom GI motility disturbances inhibit this route of feeding [158,165] .…”
Section: Probiotics Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…8514 July 14, 2014|Volume 20|Issue 26| WJG|www.wjgnet.com [212] . However, while feeding via PEG may reduce the risk of aspiration, it will not eliminate it altogether [164] , especially in patients in whom GI motility disturbances inhibit this route of feeding [158,165] .…”
Section: Probiotics Controlsmentioning
confidence: 99%
“…Since it has been shown that even in patients with normal intestinal motility both naso-and gastrojejunal tubes, once correctly positioned, will be moved in a proximal direction by the phase Ⅱ migrating motor complex, placement of enteral nutrition tubes ≥ 40 cm distal to the ligament of Treitz is considered the optimal method [165,168] .…”
Section: Probiotics Controlsmentioning
confidence: 99%
“…The development of a nasoenteral tube that would simultaneously provide a means of early postoperative gastric decompression as well as post–ligament of Treitz jejunal enteral feeding would not only satisfy the requirements of current ERAS protocols in patients undergoing major upper gastroesophageal 18 hepatobiliary and pancreatic surgery 19 but would also play an important role in the feeding of patients in the ICU who are not able to tolerate nasogastric feeding 38 . North American guidelines recommend small bowel feeding of ICU patients who are not able to tolerate nasogastric feeding 16 .…”
Section: Dual‐purpose Gastric Aspiration and Post–ligament Of Treitz mentioning
confidence: 99%
“…Although jejunal feeding is generally well tolerated, whether it modulates and impairs proper dietary protein digestion and absorption is unknown. It has been suggested that jejunal feeding requires a predigested rather than a polymeric diet (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%